1998
DOI: 10.1021/jf980515y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on the Conformation and Aggregation of β-Lactoglobulin A, B, and C

Abstract: Solutions of bovine β-lactoglobulin (β-Lg) A−C were heated at temperatures between 50 and 90 °C for 12.5 min at pH 6.7 or 7.4, and the products were analyzed by alkaline, sodium dodecyl sulfate (SDS), and two-dimensional (2D) (alkaline and then SDS) polyacrylamide gel electrophoresis (PAGE). Results from the pH 6.7 samples that were ∼70% denatured showed that the proportion of β-Lg that was in very large aggregates was β-Lg C > β-Lg B > β-Lg A. 2D PAGE showed that there were a large number of unexpected interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
161
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(179 citation statements)
references
References 53 publications
16
161
0
2
Order By: Relevance
“…Concentrations of (V, P-> *-, and y-casein, oclactalbumin, and P-lactoglobulin were determined by sodium dodecyl sulfate (SDS) polyacrylamide gel electrophoresis according to the method of Manderson et al (1998), with the following differences. Resolving gels were made from a mixture of 48.5 g of a 30% stock solution of a 37.5:1 mixture of acrylamide and N,N'-methylenebis (acrylamide), 23 g of resolving gel buffer (1.5 M Tris adjusted (at 20°C) to apH of 8.8), and 10 g of distilled, deionised water (DDW).…”
Section: Milk Analysesmentioning
confidence: 99%
“…Concentrations of (V, P-> *-, and y-casein, oclactalbumin, and P-lactoglobulin were determined by sodium dodecyl sulfate (SDS) polyacrylamide gel electrophoresis according to the method of Manderson et al (1998), with the following differences. Resolving gels were made from a mixture of 48.5 g of a 30% stock solution of a 37.5:1 mixture of acrylamide and N,N'-methylenebis (acrylamide), 23 g of resolving gel buffer (1.5 M Tris adjusted (at 20°C) to apH of 8.8), and 10 g of distilled, deionised water (DDW).…”
Section: Milk Analysesmentioning
confidence: 99%
“…At pH above 7.1 this loop is folded back to reveal the interior of the calyx. In this paper the structure of variant B at pH 7.1 is presented and compared with the structures of variant A at pH 6.2, pH 7.1, and pH 8.2 for additional insight into the structural basis of the Tanford transition and for insight into altered functionality of variants A and B of bovine BLG~Hill et al, 1996;Manderson et al, 1998!. Although preliminary results have been reported on the structures of BLGA, BLGB, and BLGC in lattice Y~Bewley et al, 1997!, the N-and C-terminal regions and several critical loops are very poorly defined.…”
mentioning
confidence: 99%
“…They postulated the prominent role of disulphide bonds. Other authors supported the view that b-Lg aggregates through a series of parallel and consecutive steps which involve both covalent (thiol/disulphide bond interchanges) and noncovalent (hydrophobically driven associations) reactions [18]. The relative proportion of these two types of interactions seems to be highly temperature-dependent.…”
Section: Nature Of Stabilising Forces Involved In Formed Aggregatesmentioning
confidence: 87%
“…In earlier studies, the formation of heatinduced disulphide-bonded dimers as intermediates was reported to be an important step in the further aggregation of b-Lg [18,22]. The presence of these intermediates at tg was determined under different protein and mineral environments.…”
Section: Formation Of B -Lg Covalent Dimersmentioning
confidence: 99%